Epitaxial growth of the candidate ferroelectric Rashba material SrBiO3 by pulsed laser deposition - G. Verdierre; N. Gauquelin; D. Jannis; Y. A. Birkhölzer; S. Mallik; J. Verbeeck; M. Bibes; G. Koster (APL Materials, 2023)
Among oxides, bismuthates have been gaining much interest due to their unique features. In addition to their superconducting properties, they show potential for applications as topological insulators and as possible spin-to-charge converters. After being first investigated in their bulk form in the 1980s, bismuthates have been successfully grown as thin films. However, most efforts have focused on BaBiO3, with SrBiO3 receiving only little attention. Here, we report the growth of epitaxial films of SrBiO3 on both TiO2-terminated SrTiO3 and NdO-terminated NdScO3 substrates by pulsed laser deposition. SrBiO3 has a pseudocubic lattice constant of ∼4.25 Å and grows relaxed on NdScO3. Counter-intuitively, it grows with a slight tensile strain on SrTiO3 despite a large lattice mismatch, which should induce compressive strain. High-resolution transmission electron microscopy reveals that this occurs as a consequence of structural domain matching, with blocks of 10 SrBiO3 unit planes matching blocks of 11 SrTiO3 unit planes. This work provides a framework for the synthesis of high quality perovskite bismuthates films and for the understanding of their interface interactions with homostructural substrates.